Salmonella serotypes, resistance patterns, and food vehicles of salmonellosis in southern Brazil between 2007 and 2012 - Roberta Capalonga; Rosane Campanher Ramos; Jane Mari Correa Both; Mara Lúcia Tiba Soeiro; Solange Mendes Longaray; Simone Haas; Eduardo Cesar Tondo (Journal of Infection in Developing Countries)
Introduction: Previous studies have identified Salmonella as the main causative agent of foodborne diseases in the state of Rio Grande do Sul (RS), southern Brazil, between 1997 and 2006. This study aimed to describe the Salmonella serotypes, antimicrobial patterns, and food vehicles of salmonellosis that occurred in RS between 2007 and 2012. Methodology: Information about Salmonella isolates and salmonellosis outbreaks registered in the official records of the Central Laboratory of RS (FEEPS/IPB-LACEN/RS) was analyzed. Results: Among the 163 isolates investigated, 138 (84.7%) were identified as S. Enteritidis. The second and third most frequent serovars identified were S. Schwarzengrund (5.5%) and S. Typhimurium (3.7%). Homemade mayonnaise was the food vehicle most frequently identified (17.39%), followed by pastry products (15.94%) and beef (12.32%). Antimicrobial resistance was analyzed; 12 drugs were tested. Higher percentages of resistance were observed to nitrofurantoin (94.2%) and nalidixic acid (89.1%). The resistance to these two drugs was verified in 80.43% of the isolates. Multi-resistance to three and five drugs was verified in four and two isolates, respectively. Conclusions: Comparing the results of the present study with results of previous reports, it was possible to conclude that S. Enteritidis and homemade mayonnaise are still the main serotype and food vehicle of salmonellosis in RS and that antimicrobial resistance has been increasing among S. Enteritidis responsible for foodborne outbreaks in southern Brazil.